Features of an enterprise development strategy based on innovation (Journal of Economic Research & Business Administration, 2016)
The article describes the features of an enterprise development strategy by analyzing the terms «strategy», «innovation» and the formation on the basis of strategic planning in enterprises. The necessity of the enterprise’s development strategy the formation on the basis of innovations mainly connected with an increase in the level of competitiveness, as evidenced by a brief overview of the evolution of the term «strategy». The content of strategy in enterprises in terms of innovation was described, which is a collection of all the constituent elements of internal processes and relations, aimed at developing a long-term development of a particular enterprise by enhancing the implementation of innovations. Disclosed objects and features of strategic management in terms of development of innovative activity. Article shows statistical data of investment on research and development in the Republic of Kazakhstan. It was understood, that the formation and implementation of innovation strategy determine the activities of the enterprise in the innovative development and allow more successfully solve many problems associated with the development, increase production efficiency and competitiveness.
Keywords: innovation strategy; innovation; development strategy; enterprise.